PROBLEMS OF TEACHING AND LEARNING VOCABULARY - Yuldasheva Dilbarkhon Saidakhmedovna (Journals Park Publishing, 2023)
A language's vocabulary is a collection of words and phrases. Students are able to effectively express themselves clearly and in detail when they are taught vocabulary in a way that enables them to have a large, comprehensive word knowledge as well as an understanding of the meanings of the words.
Keywords: vocabulary, problems in learning vocabulary, new words, vocabulary learning skills.